Studi Pendahuluan Untuk Pengembangan Indeks Kesiapan Kerja Harian - Yusuf Nugroho Doyo Yekti (Universitas Serang Raya, 2018)
Work related accident is a problem that needs to be considered seriously in Indonesia. The number of occupational accidents is increasing significantly from 96,314 in 2009 to 110,285 in 2015. The mortality rate in these cases is very high. This research aims to develop a daily fitness for duty index as a measurement to ensure that workers are able to work effectively and safely. Systematic literature review had been carried out through several stages, i.e. 1) determination of searching strategy, and searching process, 2) determination of searching criteria, 3) quality control for literature, and 4) conclusion. The experiment involved four participants. They divided into two groups: night shift workers and morning shift workers. Total sleep time, heart rate at rest, reaction time, and body weight were recorded during the experiment. The daily fitness for duty index has been developed that consider sleep sufficiency factor, circadian cycle misalignment factor, and individual factor. The daily fitness for duty index has a strong correlation with subjective work readiness measurement. Therefore, it can be concluded that the daily fitness for duty index is trustworthy to measure fitness for duty.